"Einen guten Flügel und auch ein gutes Clavicord haben" - Speerstra, Joel (Muzikološki zbornik, 2011)
Studying the haptic feedback of various instruments within a historical keyboard instrument landscape raises questions about why C. P. E. Bach, among others, encouraged practicing musicians to engage with the phenomenology of multiple keyboard instruments, in order to develop musicianship at all of them.
Keywords: artistic research; clavicord; čembalo; haptics; haptični vtisi; harpsichord; klavikord; organologija; organology; umetniško raziskovanje